Existential Urgency: Contemporaneity, Biennials and Social Form - Osborne, Peter (The Nordic Journal of Aesthetics, 2016)
What happens to the form of the biennial when biennials become part of a world system of art institutions, subject to the historical temporality of a global contemporaneity? In particular, what happens when the periodic rhythms of national narratives of biennial exhibitions are overcoded by a serial sequence of international biennials – competing for contemporaneity – seemingly without end? This essay approaches these questions via a consideration of the debate about the transitional symbolic significance of the 1989 Third Havana Biennale. It contrasts three historical problematics of ‘the contemporary’ as models through which to think the cultural function of biennials: (i) the critique of anthropology, or, the coeval; (ii) socialist post- coloniality, or the avant-garde construction of traditions; (iii) the historical contemporaneity of a global capitalist modernity.